THE IMPLEMENTATION OF TUTORIAL VIDEO IN LEARNING WRITING ON PROCEDURAL TEXT - Asep Kiki; Zubaedah Wiji Lestari; Nuriska Noviantoro (JALL (Journal of Applied Linguistics and Literacy), 2022)
In learning, a language teacher need a media to support the activity. Teaching media is a tool to make teaching learning process run effectively and efficiently. Tutorial video is a video to transfer information about how to achieve something through a set of instruction. This study aimed to analyze the implementation of tutorial video in learning writing on procedural text and to analyze the students’ responses towards the use of video in learning writing on procedural text. This research was conducted with a qualitative approach with a case study. The obervation, test, questionnaire and interview were used in collecting the data. The participant of this research were 30 students of X IPA in SMA Muhammadiyah Rancaekek. The result showed that by tutorial video helped their learning writing process and enhance their writing skill especially in vocabulary and content on procedural text. Therefore, this research conclusion showed student had good impact in their learning writing process and had positif responses on enhance their writing skills on procedural text.